Pemberdayaan UMKM Desa melalui Inovasi Produk dan Digitalisasi Pemasaran - Sarma, Dimas Titan Putra; Purnama , Sindi Ade; Andini , Puja; Nata , Fandwi; Sapitri , Wulan; Alvionah , Tia; Effendi , Yanto; Gayatri, Ida Ayu Made Er Meytha; Soleh, Ahmad (Jurnal Kewirausahaan & Inovasi, 2025)
The Community Service Program (KKN) is part of student community service, one of which is through village economic empowerment. [Village Name] Village, as the location of KKN, has quite large economic potential through Micro, Small, and Medium Enterprises (MSMEs) activities, especially in the processed food and craft sectors. However, MSMEs in this village still face various obstacles such as lack of product innovation, limited packaging, and suboptimal digital marketing.  The purpose of this activity is to help village communities, especially MSMEs, to develop product innovation and utilize digital technology as a marketing medium. Activities are carried out through observation, participatory training, and direct assistance to MSMEs. The results of the program show an increase in the ability to develop products and packaging, as well as the courage to utilize social media as a means of promotion. It is hoped that this activity can continue to be developed by the village government and become the first step towards community economic independence.